Disaster Mitigation Communication Model as an Effort to Manage Disasters in South Kalimantan Province (Case Study on Flood Disaster in South Kalimantan Province) - Hayat, Muzahid Akbar; Mardiana, Mardiana; Sari, Ade Nur Atika; Ronianysah, Ronianysah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to understand communication strategies in flood disaster risk mitigation in South Kalimantan Province which has a high level of vulnerability. Using a descriptive qualitative research method, this study analyzes social and cultural phenomena that contribute to community preparedness. The results of the study indicate that effective disaster communication, based on innovation diffusion and active community participation, can improve preparedness and reduce the impact of disaster risk. Areas such as Hulu Sungai Tengah, Barito Kuala, and Banjar Regencies require a special approach that considers geohydrological analysis and local conditions. Jaranih and Jejangkit Villages, for example, require community-based strategies such as strengthening volunteers and building evacuation infrastructure. In addition, strengthening Disaster Resilient Villages (Destana) through training and community empowerment is a significant strategic step. The disaster mitigation communication model led by BPBD and integrated with related agencies shows effectiveness in strengthening coordination between the government and the community, in accordance with Law No. 24 of 2007. With this approach, disaster responses can be carried out quickly, precisely, and efficiently. This study emphasizes the importance of synergy between the government, related institutions, and the community in building a sustainable emergency response culture.